The impact of foreign direct investment on economic growth in Lesotho - Nkhasi, Rethabile (School of Economics, 2025)
This study evaluates the impact of the inflow of foreign direct investment (FDI) on Lesotho's economic growth in both the short- and long-run from 1977 to 2020. Three versions of the exogenous model guided by Solow (1956), Mankiw Gregory et al. (1992), and World Bank (1990) and augmented by FDI are used and then estimated by the Auto-Regressive Distributed Lag (ARDL) approach to cointegration. The findings show that FDI's influence on economic growth is negligible, while capital investment (i.e. gross fixed capital formation) and human capital induce economic growth in both the long-run and the short-run. It is also noted that population growth is detrimental to economic growth in both periods whereas trade openness only exerts a positive influence on economic growth in the long-run. The policy implications that are derived from this study suggest amendments in land allocation policies and increased governmental support for the investment promotion agency, LNDC, which currently relies on limited income sources. Moreover, the paper recommends that policymakers boost technological progress by regularly updating school curricula and promoting trade, particularly in tech-intensive sectors.